Neuroplasticity in Multiple Sclerosis: Implications for Rehabilitation - Srishti Bipul Banerjee (Journal of the Scientific Society)
Multiple sclerosis (MS) is an autoimmune disorder of the central nervous system characterized by demyelination, followed by neurodegeneration. Inflammation, demyelination, and neurodegeneration form the hallmark of MS. The demyelinated lesions get repaired by the process of remyelination. It has been found that the functional reserve of the brain remains viable in MS; hence, the brain has the capacity to undergo adaptive plasticity which plays a major role in clinical recovery. Neuroplasticity occurs at two sites, namely, (1) locally at the site of injury, known as sensory reorganization, and (2) in the distant uninjured areas of the brain, particularly the hippocampus and the default mode network. To achieve enhanced and enduring clinical outcomes, it is essential to implement physiotherapy interventions based on the principles of neuroplasticity. These treatment interventions include bimanual upper extremity training, rehabilitation in functional activities, aerobic training, software-based cognitive training, use of assistive technology, hand rehabilitation robotics, virtual reality, and exergaming. All of these treatment interventions have proven underlying neuroplastic changes that improve treatment outcomes.